[Kalendarz na rok 1986 wydany przez Konfederacja Polski Niepodległej] . Calendar for 1986 by Confederation of Independent Poland - Konfederacja Polski Niepodległej (KPN) - II Obszar Kraków. (Konfederacja Polski Niepodległej, 1986)
B&w print on white paper. The calendar includes a graphic image of the national emblem of Poland (eagle in a crown) with the symbol of the WW II Polish underground state ("Polska Walcząca" - letters "p" and "w" merged). Price: 100 zł.